Prevalence of metabolic syndrome and diabetes mellitus in Sami and Norwegian populations. The SAMINOR—a cross-sectional study - Broderstad, Ann Ragnhild; Melhus, Marita (BMJ Open, 2016)
Published version. Source at http://dx.doi.org/10.1136/bmjopen-2015-009474 Objectives: Metabolic syndrome (MetS) is recognised as a reliable long-term predictor of adverse health outcomes. Elevated prevalence rates of MetS and chronic lifestyle diseases have been documented in different indigenous groups. We aimed to evaluate the prevalence of MetS and diabetes mellitus in relation to ethnicity in Northern Norway. In addition, we discussed different cut-off values for waist circumference (WC) and what impact this has on the prevalence of MetS. Materials and methods: SAMINOR is a population-based study of health and living conditions in areas home to Sami and non-Sami populations. The survey was carried out in 2003–2004. All eligible residents in specific age groups were invited. In total, 16 538 males and females aged 36–79 years participated and gave informed consent for medical research. Results: This study involved a total of 7822 female and 7290 male participants. Sami affiliation was reported by 5141 participants (34%). The prevalence of MetS was high in both ethnic groups independent of which WC cut-off value was used. No ethnic differences in prevalence of diabetes mellitus were demonstrated. However, ethnicity appeared to affect diabetes treatment, which was more prevalent among Sami than non-Sami women. Conclusions: In this study, there was no ethnic difference in diabetes prevalence, but ethnicity appeared to affect diabetes treatment. Tablet treatment was more commonly in use among Sami women than among non-Sami women. We demonstrated a high share of negative metabolic components. These metabolic components have important health implications. Therefore, determining preventive initiatives is important in the primary and specialist healthcare system. These initiatives must be made culture and linguistic